An Analysis of Physiological Workload on Pure Coconut Oil Production Process - Yulinda Sakinah Munim,; Sandi Rais,; Lita Asyriati Latif,; Sahdar Radjak,; Syarif Al Fajrin, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This study aims to analyze the physiological workload in the virgin coconut oil production process based on energy expenditure evaluations and determine rest periods to ensure that work does not require excessive energy. Assessment of workload objectively using pulse indicators and energy consumption (energy cost) observations at the four stages of the virgin coconut oil production process, namely the process of stripping the coconut husk, the process of cutting the coconut shell, the process of grating the coconut and the process of cooking the coconut milk. The energy expenditure of workers in the coconut coir stripping section is 5,138 kcal/min, the coconut shell cutting section is 2,552 kcal/min, the coconut meat grating section is 3,575 kcal/min, and the coconut milk cooking section is 2,885 kcal/min. Hence the coco coir stripping workstation is included in the heavy workload category with an average cardiovascular load value of %CVL of 56%, which means that the work needs to be improved; the recommended work-rest cycle for workers at the coco peeling workstation is 47 minutes. The workstation for cutting coconut shells to cooking coconut milk is included in the category of moderate workload with a value of %CVL ≤33%, still within the recommended workload limit.